Pemanfaatan Minyak Cengkeh (Syzygium aromaticum) sebagai Biosedatif Alami untuk Meningkatkan Kelangsungan Hidup Benih Patin Siam (Pangasius hypophthalmus) selama Transportasi Sistem Tertutup - Rozik, Mohamad; Matling, Matling; Mukstofa Carda, Muhammad Aldair; Ladio, Andre; Maryani, Maryani (Universitas Batangahari Jambi, 2025)
This study aimed to evaluate the effectiveness of clove oil (Syzygium aromaticum) as a natural anesthetic for closed-system transportation of striped catfish fry (Pangasius hypophthalmus). Three clove oil doses (4, 5, and 6 mL per container) were tested for induction time, anesthesia duration, and fish survival rate during eight hours of transportation. The results showed that the 5 mL dose was optimal, with an induction time of 0.38 ± 0.05 minutes, anesthesia duration of 120 ± 3.6 minutes, and a survival rate of 70%. The 4 mL dose produced the highest survival rate (83.3%) but showed less stable anesthetic effects, while the 6 mL dose reduced survival due to eugenol toxicity. Water quality parameters (temperature 28.8–30.7°C; pH 6.7–7.2; DO 6.2–7.3 mg/L) remained within optimal ranges. Therefore, clove oil is effective as a natural anesthetic to reduce stress and maintain the survival of striped catfish fry during closed-system transportation